(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
In recent years, decommissioned historic structures have been repurposed for private or public use. Sector consumes over a third of global final energy and create a large amount of CO2. The need to comply with energy conservation rules in both new and existing buildings has encouraged planning and engineering practices aimed at reducing carbon dioxide emissions while simultaneously improving interior comfort as well as functionality. In this article, a devoted scientific effort must be expended when dealing with historical structures that require to maintain their essential testimony knowledge into society. As a result, customized retrofit methods have been explored and executed without jeopardizing the architectural integrity of the buildings, particularly where new uses are anticipated. This research classifies the utilization of energy efficiency technologies as well as the deployment of renewable energies in historic buildings, including such solar and geothermal energies, and heat pumps as well as other high-efficiency heating, ventilation, and air conditioning units.